Expression of granulocyte-macrophage colony-stimulating factor in rheumatoid arthritis: regulation by tumor necrosis factor-alpha. - Haworth, C; Brennan, F; Chantry, D; Turner, M; Maini, R; Feldmann, M (1991)
Granulocyte-macrophage colony-stimulating factor (GM-CSF), in addition to being a growth factor for granulocytes and macrophages, is an activator of cells of the monocyte/macrophage lineage and induces HLA class II expression and cytokine synthesis in these target cells. Macrophage activation and class II expression are prominent features in rheumatoid arthritis (RA) joints, but the mechanism of their stimulation is not understood, since interferon-gamma, the major stimulus of class II expression, is not usually detectable at the protein level in synovial cell culture supernatants. We have, therefore, studied GM-CSF expression in cultures of cells derived from joints affected by RA and osteoarthritis (OA), and show that GM-CSF is produced spontaneously both by RA synovial cells and to a lesser extent by OA synovial cells in the absence of extrinsic stimuli. GM-CSF production continues for the 5-day duration of the culture period. Using neutralizing antibodies to tumor necrosis factor (TNF)-alpha we demonstrated that GM-CSF production in RA synovial cell cultures is dependent on the continued presence of active TNF-alpha. This result supports our concept that continued activation of the cytokine network is a marked feature of RA, and that TNF-alpha plays a pivotal role in this network, by regulating the production of other pro-inflammatory cytokines, such as interleukin 1, as demonstrated previously, and GM-CSF.